A new single-phase white-light-emitting CaWO4:Dy3+ phosphor: synthesis, luminescence and energy transfer1. Issue 77 (22nd August 2015) - Zhang, Yang; Gong, Weitao; Yu, Jingjie; Pang, Hongchang; Song, Qiang; Ning, Guiling
<x xml:space="preserve">Abstract</x> A new single-phase white-emitting CaWO4:Dy3+ phosphor has been successfully synthesized and the photoluminescence properties and energy-transfer mechanism have been carefully investigated.